A functionalised carbon nanotube system for targeting of inflammatory biomakers in ischemic stroke - Komane, Phogothi Patrick (My University, 2019)
Stroke is the fourth leading cause of death in the United States after cardiac disease and cancer, the third major cause of death in the developed countries, the second most common cause of dementia and death and the leading cause of disability worldwide. Prevalence of stroke is expected to increase significantly around the world in the years ahead as the global population older than 65 years of age continues to increase by approximately 9 million people per year. The global economic impact of stroke may be dire if effective preventive measures are not implemented to help decrease the burden of this disease. The use of the current diagnostic tools such as Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) is limited by availability, cost and radiation exposure. The current treatment of stroke with thrombolytic agents such as recombinant Tissue Plasminogen Activator (rTPA) and anti-inflammatory agents such as glucocorticoids namely methylprednisolone and dexamethasone have some drawbacks which need to be dealt with in order to use these glucocorticoids for the intended purpose. The therapeutic potential of these corticosteroids is negatively affected by their short circulatory half-lives and poor pharmacokinetics requiring administration of higher doses which could lead to serious systemic side-effects. Nevertheless, nanotechnology has demonstrated promising results in resolving the shortcomings of the present diagnosis and therapy of ischemic stroke. Nanomedicine is an emerging field of medicine where engineered nanomaterials are utilized for the detection, treatment and prevention of certain diseases including neurological disorders. Carbon nanotubes (CNTs) are a new group of nanomaterials that has demonstrated promising outcomes for the advancement in technology in the field of medicine. They have a variety of unique properties making them useful tools in neurobiological applications. Based on their outstanding physico-chemical properties, carbon nanotubes have the potential to be employed as theranostic tools for ischemic stroke diagnosis and treatment. In this study, vertically aligned multiwalled carbon nanotubes were synthesized, purified, functionalized, PEGylated and dexamethasone loaded for delivery to the ischemic brain tissue site. In addition, atrial natriuretic peptide (ANP) antibody and FITC, a fluorescent tag were attached to this complex for targeting of the ischemic site and tracking of the bionanomaterial. The conditions for optimal synthesis of carbon nanotubes were optimized using Box-Behnken Design of Experiments in order to produce multiwalled carbon nanotubes with vertical alignment, high yield, length and internal and external diameters suitable for application in diagnosis and treatment of neurological disorders. Pyrolysis conditions of chemical vapour deposition of MWCNTs were as follow; carrier gas = 95 % argon balanced with 5 % H2, catalyst = 2,5 % ferrocene, substrate = silicon wafer, gas flow rate = 400 mL.min-1, synthesis temperature = 775 °C and synthesis duration = 45 min. Vertically aligned MWCNTs with average length of 127 μm, average internal diameter of 11 nm and average external diameter of 73 nm were obtained under these conditions. Morphological changes were confirmed by SEM and TEM. Addition of functional groups to MWCNTs was demonstrated by FTIR and Raman Spectroscopy. Thermal stability of functionalized MWCNTs was determined by TGA. A drastic increase in weight loss was observed at 150 °C and 700 °C up to 775 °C and 825 °C in functionalised and pristine MWCNTs respectively. The surface area increased from 47,156 cm2 (pristine CNTs) to 144,096 cm2 (functionalized CNTs) as shown by BET. The presence of carbon at 2Ө of 25 ° and iron at 2Ө of 45 ° in MWCNTs was illustrated by XRD. They were found to be strongly electrically conductive by PPMS at temperatures from 36.85 °C - 76.85 °C when temperatures from -73.15 °C to 76.85 °C were used. The CNT yield was also found to be improved by a mixture of Fe/Co and 599.40 mg of CNTs were produced compared to 331.2 mg produced when Fe/Ni was used. Honeycomb like structures were formed on the surface of the CNTs when treated with 5 M HCl. Polydispersive index and zeta potential were found to be 0.261 and -15.0 mV, respectively. Dexamethasone release increased by 55 %, 65 % and 95 % in pH of 7.4, 6.5 and 5.5 respectively as evaluated by UV-VIS. The functionalized VA-MWCNTs were demonstrated to be less toxic in PC-12 cells in the concentration range from 20 – 2000 μg.mL-1. The functionalized MWCNTs were intravenously injected in stroke induced Sprague Dawley rats to assess their effect in the treatment of stroke. Stroke induced rats, when treated with the functionalized MWCNTs, a great improvement in their health was observed as demonstrated by reduction of eye sunkenness, fading of the redness of the eye and rat circling in all directions. The levels of ANP were higher in the stroke induced and dropped after treatment with the functionalised MWCNTs. MWCNTs were also distributed to various organs as confirmed by biodistribution studies using Fluorescence microplate reader. These findings have demonstrated the potential of VA-MWCNTs in the enhancement of fast and prolonged release of dexamethasone which could lead to the effective treatment of ischemic stroke as confirmed by reduction in the sunkenness of the left eye, fading away of redness of the eye and circling of the rat in all directions when suspended by the tail in the MWCNTs-treated CCAO rats.
A Thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg,2019
Keywords: Immunotherapy--methods; Cerebrovascular disease; Genetic Markets